Design of local product marketing system in sungai lebung village web-based - Karnadi; Gunawani; Muhammad Ihsan (Yayasan Pendidikan Rafisqy Arfadhia, 2023)
In Sungai Lebung Village, South Pemulutan District, Ogan Ilir Regency, from year to year there are still many people who have local product businesses who don't know much about the development of information technology at this time, not to mention during the COVID-19 pandemic, many people who have businesses are affected. difficulties in how to market local products that exist in Sungai Lebung Village and until now there is still no solution how to handle and help business people to be able to do local product marketing practically. Therefore, to overcome these problems, researchers are trying to provide solutions by designing and creating a website application for a local product marketing system in Sungai Lebung Village and the authors hope to overcome the problems affected by local product business actors in Sungai Lebung Village, South Pemulutan District, Ogan Ilir Regency. . The design of a local product marketing system in the Sungai Lebung Village based on the website is a new concept that can be described as the marketing process of buying and selling goods in Sungai Lebung Village on the World Wide Web on the Internet or the process of buying and selling or marketing products in the Sungai Lebung Village through internet information network wesite the method used in this research is, experimentation to design and build an online sales store application, e-commerce with PHP Visual studio code programming language, HTML tags and utilizing mysql database as a database server. development of an even more attractive appearance, namely reducing user convenience..